Analisis Peran Pendamping dalam Meningkatkan Kapasitas Pengrajin Gula Aren di PT Sentra Mulia Sejahtera Gorontalo - Noval Moha; Asda Rauf; Amelia Murtisari (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Indonesia is an agricultural country where the agricultural sector still plays a crucial role in the economy. One of the agricultural commodities with high economic value is aren (Arenga pinata merr), which is widely used in the production of aren sugar. This study aims to analyze the role of mentors in enhancing the knowledge and skills of aren craftsmen at PT. Sentra Mulia Sejahtera, Limboto District, Gorontalo Regency. The research methodology employed is a qualitative descriptive approach using survey techniques and the Slovin formula. Data was collected through interviews and questionnaires conducted over a three-month period from July to September 2024, involving 39 respondents comprising mentors and palm sugar artisans. The data was analyzed using multiple linear regression to test the influence of the facilitator's role as a facilitator, communicator, motivator, and innovator on the knowledge and skills of the artisans. The results of the study indicate that the roles of facilitator and innovator have a positive and significant influence on the improvement of artisans' knowledge and skills. Conversely, the roles of communicator and motivator showed a significant negative influence, indicating weaknesses in communication and motivation. These findings imply the need to strengthen assistance strategies, particularly in the roles of communication and motivation, in order to improve the capacity of palm sugar craftsmen more comprehensively.